2012
DOI: 10.1177/0003319711434054
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Unrecognized Diabetes Mellitus in Patients Admitted With Acute Coronary Syndrome

Abstract: We assessed the prevalence of unrecognized diabetes mellitus (DM) in patients with acute coronary syndrome (ACS) as determined by elevated glycosylated hemoglobin (HbA1c), fasting plasma glucose (FPG), and random plasma glucose (RPG) levels. This prospective study recruited 583 patients admitted with ACS without previous diagnosis of DM during 1-year period. Glycosylated hemoglobin was checked for most patients especially those with high values of FPG and or RPG. Patients were classified according to their gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Finding accurate indicators which can be used to determine the prognosis of these patients emerges as a target of interest. In our study, we analyzed the general conditions and comorbidities in DM and non-DM patients, and the ratio of DM in the observed Chinese ACS octogenarians was over one third, which was higher than the prior reports by about 20-30% [33,34]. The Cys C level was significantly different, while severity of coronary artery (Genesis score), GRACE risk score as well as general renal function indicators were not significantly different between DM and non-DM patients.…”
Section: Discussionmentioning
confidence: 77%
“…Finding accurate indicators which can be used to determine the prognosis of these patients emerges as a target of interest. In our study, we analyzed the general conditions and comorbidities in DM and non-DM patients, and the ratio of DM in the observed Chinese ACS octogenarians was over one third, which was higher than the prior reports by about 20-30% [33,34]. The Cys C level was significantly different, while severity of coronary artery (Genesis score), GRACE risk score as well as general renal function indicators were not significantly different between DM and non-DM patients.…”
Section: Discussionmentioning
confidence: 77%
“…Prevalence of glucose abnormalities among patients with no previous history of diabetes presenting with ACS in previous studies vary between 21% -84% (8,9). A study conducted in urban India revealed that 84% of patients with ACS with no previous history of diabetes have abnormalities in glucose metabolism based on the findings of OGTT (10).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study from the Middle East had demonstrated similar incidence of stress hyperglycemia and unrecognized diabetes in ACS patients with no prior diagnosis of diabetes. [17]…”
Section: Discussionmentioning
confidence: 99%